Analisis Hukum Aksi Balasan Tiongkok Menaikkan Tarif Impor Terhadap AS dalam Kerangka Hukum Penyelesaian Sengketa WTO - Suaibatul Aslamiyyah; Mika Anwarita; Edi Junaidi; Suharti Rossani Aritonang; Ribka Yuniar; Ade Maulia Cahyani; Febriana Adtikah Sari; Carissa Intan Ramadhani; Eplin Alperedoh (PT PUSTAKA CENDEKIA GROUP, 2025)
The increase in import tariffs imposed by the United States on Chinese products has triggered an escalation of international trade conflicts commonly referred to as a trade war. In response, China adopted retaliatory measures by raising import tariffs on products originating from the United States. This study aims to analyze the legality of such retaliatory actions within the framework of the dispute settlement system of the World Trade Organization (WTO). The research employs a normative juridical method using statutory and conceptual approaches, through an examination of the provisions of the General Agreement on Tariffs and Trade (GATT) 1994 and the Dispute Settlement Understanding (DSU). The findings indicate that although the actions of the United States potentially violate its bound tariff commitments under the WTO, China’s retaliatory measures undertaken without authorization from the Dispute Settlement Body (DSB) are also inconsistent with the WTO dispute settlement mechanism. This study underscores the importance of compliance with the multilateral dispute settlement system in order to maintain stability in international trade.